Parenting: Model Pengasuhan Membangun Kecerdasan Emosi dan Kemandirian Keluarga Di Desa Wisata - Ni Luh Putu Yunianti Suntari; I Nyoman Ribek; Dewa Gede Nata Raditya; Ni Made Yuni Gumala (Ilin Institute, 2024)
Changes in the social order, from industry to information, have an impact on the global flow of information that cannot be stopped. Every individual, young and old, is busy responding to the rapid flow of change. And this has an impact on people’s traditional communication patterns, especially families. Family members no longer have time to chat together, discuss finishing or carry out activities together. As a result, many events colourfull the growth and development process of children, especially teenagers, escape the attentioan of parents. Several causal factors include the inscreasing role of parents in society, family ignorance in carrying out child care in conditions like today. Parents need guidance to helping their children grow and develop. This service aims to help families care for their children. By using parenting guides, as finding/result from previous research. This guide was then developed into a module that is easy for families to use in guiding teenagers to face the influence of globalization. This service activity shows the results of increasing parents’ understanding of the parenting patterns especially regarding emotional intelligence and family independence as applied to their children. In one session, the service team also had the opportunity to interact and dialogue directly with parents regarding things they encountered during parenting. It is hoped that the benefits obtained by families can apply this appropriate parenting model to every interaction thar occurs in the family.